Sosialisasi QRIS: Peluang dan Tantangan Digital Keuangan Desa (Studi Kasus Desa Bandar Baru Kec. Sibolangit Kabupaten Deli Serdang) - Dinda Ayu Khairunisa; Salsabila Balqis; Gafa Anjasyah Putra; Bagus Ramadi (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The rapid development of digital technology has brought significant changes to payment systems in Indonesia, including rural areas. One of the key innovations introduced by Bank Indonesia is QRIS (Quick Response Code Indonesian Standard), which aims to simplify cashless transactions and promote financial inclusion. This study aims to describe the process of QRIS socialization in Bandar Baru Village, Sibolangit District, Deli Serdang Regency, as well as to identify the opportunities and challenges faced by the community in its implementation. The activity was carried out in three stages: material presentation, question-and-answer sessions, and hands-on practice in using QRIS. The results show that most participants were initially unfamiliar with digital payment systems; however, after the socialization activities, their level of understanding increased significantly. The community began to recognize the benefits of QRIS as an efficient, secure, and practical payment method that supports the growth of micro, small, and medium enterprises (MSMEs). Nevertheless, the main challenges identified include low digital literacy, limited internet access, and concerns about transaction security. This socialization initiative is expected to serve as an initial step in expanding the adoption of digital payment systems at the village level, fostering a technologically literate society and supporting inclusive and sustainable economic growth